The role of cooperatives in marketing arabica coffee: A case study of the Benteng Alla Farmers' cooperative in Enrekang Regency, South Sulawesi, Indonesia. Issue 2 (July 2021) - Busthanul, N; Summase, I; Syafiuddin, M; Heliawaty; Ibrahim, T; Rukka, R M.; R, Abdul
Abstract: Cooperatives are a product of the government's efforts to improve the national economy. The agricultural sector is the backbone of the national economy, so if the cooperative in the agricultural sector functions properly, it will greatly assist in improving the national economy. The purpose of this study was to analyze the role of the Benteng Alla Farmers' Cooperative in marketing Arabica coffee, and to analyze the development strategy of the Benteng Alla Farmers' cooperative in Marketing Arabica Coffee. The analysis technique used is the SWOT analysis. The results of this study indicate that the Benteng Alla farmer s' cooperative is not only used as a forum for members to gather but a place where they can gain experience and knowledge about the activities carried out by the cooperative, and with the cooperative it will also build farmers and rural communities who have quality human resources excellence which includes increasing expertise and skills (business and organization), knowledge, and developing the entrepreneurial spirit of the farmers themselves.